Meta-Analysis of Factors Associated With Sustained Viral Response in Patients on Hemodialysis Treated With Standard or Pegylated Interferon for Hepatitis C Infection (Iranian Journal of Kidney Diseases, 2010)
Introduction. The efficacy and safety of pegylated and standard interferon (IFN) have been scrutinized in meta-analyses; however, factors associated with hepatitis C viral response in patients on hemodialysis are not well investigated.Materials and Methods. We evaluated factors that could be associated with sustained virological response (SVR) to pegylated or standard IFN monotherapy in patients on hemodialysis with chronic hepatitis C virus (HCV) infection, by performing a systematic review of the literature with a meta-analysis of clinical trials. We used both Mantel-Haenszel and DerSimonian and Laird random effects models, with heterogeneity and sensitivity analyses.Results. Twenty-one studies on IFN-alfa2a or IFN-alfa2b (491 patients) and 12 on pegylated-IFN-alfa2a or PEG-IFN-alfa2b (279 patients) were evaluated. The pooled SVR for standard and pegylated IFN monotherapy in random effects model was 39.1% (95% confidence interval [CI], 32.1 to 46.1) and 39.3% (95% CI, 26.5 to 52.1), respectively. Pooled dropout rates were 22.6% (95% CI, 10.4 to 34.8) and 29.7% (95% CI, 21.7 to 37.7), respectively. Female gender, HCV-RNA copies per milliliter, HCV genotype, alanine transaminase pattern, duration of infection, liver fibrosis stage, and treatment duration were not associated with SVR. Only an age less than 40 years was significantly associated with SVR in both models (odds ratio, 2.17; 95% CI, 1.03 to 4.50).Conclusions. Additional benefit of monotherapy with pegylated IFN in patients on hemodialysis with HCV infection in terms of viral response and adverse events is still unclear. According the current literature, younger age was the only determinant of SVR.